Analisis Dampak Kerusakan Jalan dengan Menggunakan Metode PCI Jalan Poros Jendral Ahmad Yani Kota Parepare - Faidlul Haqriyadi; Adnan Adnan; Hamka Hamka (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Pavement conditions affect the comfort, security and safety of road users. However, pavement conditions are increasingly decreasing due to road damage factors that can be divided into two parts, namely structural damage which includes pavement failure or damage to one or more pavement components that result in the pavement no longer being able to bear traffic loads, and functional damage which includes safety and comfort. This study aims to analyze the level of road damage using the PCI method. The results of the study showed that the average value of damage to the main road section of General Ahmad Yani Km 7, Parepare City was 38, which indicated that the quality of the road pavement was in fair condition with a level of road damage to Alligator cracking of 11%, longitudinal cracking of 7%, potholes of 10%, patching and utility cut patching of 60%, weathring/raveling of 2%, depression of 3%, curvature of 6%, swell of 05%, and shoving of 1%.